Electrical product compliance and safety engineering - Loznen, Steli, 1952-; Bolintineanu, Constantin; Swart, Jan (Electrical engineer) (Artech House technology management and professional development library., 2017)
This comprehensive resource is designed to guide professionals in product compliance and safety in order to develop more profitable products, contribute to customer satisfaction, and reduce the risk of liability. This book analyzes the principles and methods of critical standards, highlighting how they should be applied in the field. It explores the philosophy of electrical product safety and analyzes the concepts of compliance and safety, perception of risk, failure, normal and abnormal conditions, and redundancy. Professionals find valuable information on power sources, product construction requirements, markings, compliance testing, and manufacturing of safe electrical products.